2015
DOI: 10.1186/s13567-015-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

A broad spectrum screening of Schmallenberg virus antibodies in wildlife animals in Germany

Abstract: To identify native wildlife species possibly susceptible to infection with Schmallenberg virus (SBV), a midge-transmitted orthobunyavirus that predominantly infects domestic ruminants, samples from various free-living ruminants, but also carnivores, small mammals and wild boar were analyzed serologically. Before 2011, no SBV-specific antibodies were detectable in any of the tested species, thereafter, a large proportion of the ruminant population became seropositive, while every sample taken from carnivores or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 26 publications
7
32
1
2
Order By: Relevance
“…Decline in the percentage of SBV‐seropositive yearlings from 2013 to 2014 suggests lower exposure of those animals to the virus indicating a decrease in SBV circulation. Similar dynamics of SBV infections was also observed in wild ruminants in Germany with the decrease of SBV‐seropositive animals in 2013/2014 hunting season (EFSA, ; Mouchantat et al., ). Only three of 12 (25%) European bison born in 2014 had SBV antibodies; these results are likely to be due to passive immunity rather than an acute infection, especially considering the high seroprevalence rates in their mothers.…”
Section: Discussionsupporting
confidence: 64%
“…Decline in the percentage of SBV‐seropositive yearlings from 2013 to 2014 suggests lower exposure of those animals to the virus indicating a decrease in SBV circulation. Similar dynamics of SBV infections was also observed in wild ruminants in Germany with the decrease of SBV‐seropositive animals in 2013/2014 hunting season (EFSA, ; Mouchantat et al., ). Only three of 12 (25%) European bison born in 2014 had SBV antibodies; these results are likely to be due to passive immunity rather than an acute infection, especially considering the high seroprevalence rates in their mothers.…”
Section: Discussionsupporting
confidence: 64%
“…However, not so much is known about other prevalent viral diseases of swine such as porcine circovirus type 2 (PCV-2), porcine reproductive and respiratory syndrome virus (PRRSV), influenza A virus (IAV), porcine parvovirus (PPV) (Gonzáles-Barrio et al, 2015;Sliz et al, 2015;Touloudi et al, 2015). Unexpectedly, specific antibodies against Schmallenberg virus (SBV) were detected in wild boars (Mouchantat et al, 2015). Despite of the fact that enteric viruses are significant pathogens of domestic pigs, they have been studied only sporadically in wild boar.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemics swept through the European continent in 2011-2012 and reemerged in 2014 [11,12]. The presence of viral genome has been confirmed in various ruminants (cattle, sheep, goat, elk, and wildebeest) and serology tests indicated that a number of additional species (bison, deer, mouflon, and chamois) are also susceptible to SBV infection [13][14][15][16][17]. In adult hosts, SBV infection typically results in subclinical infection or moderate clinical signs, such as fever, decreased milk production, or diarrhoea.…”
Section: Introductionmentioning
confidence: 99%